Outorga de direito de uso de recursos hídricos na bacia hidrográfica do rio Sergipe - Oliveira, Mário Sérgio dos Santos (2011)
Water is vital for human s activity development and its use has to be permitted by a water Grant. The water grant s legal definition given by the law nº 9433/97 express the sustainable development principle, since its purpose is to quarantee water uses control in terms of quality and quantity, and also enable the acess of water implicitly to present and future generations. In this context, the-main goo of this Master thesis is to verify if water grant it self can be considered on instrument to the sustainable development. The question alluded us to the study of the Sergipe River water shed for its importance in the context of political, economic, social and cultural development of the state. During the researches, was verified that the water grants given made the economic activities development possible, but did not provide the environmental sustainability, never the less, the main result of this study is to find that water grant, in basin, only can be considered sustainable, in other words, became on instrument to promote the sustainable development, if they are implemented within a feedback water management instruments system, within on integration between user s sectors and water resources management sector, the preservation of multiple uses and water s quality and quantity indissolubility, and also the existence of water inspection on the users granted and now granted to quarantee the carry out of the law and the penalties application.